Wired to the world, chained to the home : telework in daily life - Gurstein, Penny (UBC Press, 2001)
Gurstein combines a background in planning, sociology of work, and feminist theory with qualitative and quantitative data from ten years of original research, including in-depth interviews and surveys, to understand the socio-spatial impact of home-based work on daily life patterns. She analyzes the experiences of teleworkers including employees, independent contractors, and self-employed entrepreneurs, and presents significant findings regarding the workload, mobility, the distinct differences according to work status and gender, and the tensions in trying to combine work and domestic activities in the same setting. As organizational structures, technology, and family priorities continue to change, the often overlooked phenomenon of teleworkers has important implications on everything from employment policies to community planning and design.[publisher].